Rules of Government Secrecy in the Law of Archives in Indonesia - Prastyo, Brian Amy (UI Scholars Hub, 2013)
Every government operates secrecy as one of mechanism to protect the state, the people, and the assets from threats. There is lack of clarity of rules for the secrecy system in Indonesia. Ultimately, there is no uniform conception among government officials, because each agency makes its own policy and system. This condition brings disadvantage to society, because there is no clear guidance on this subject and it will not be able to push the government to act more responsible in managing the information. The rules about “closed archives” in Law No. 43 of 2009 about Archives and the term of “security classification” that mentioned in Government Regulation No. 28 of 2012 about the Implementation of Law No. 43 of 2009 about Archives, do not help at all in solving that problems. To get the accountability in the management of closed archive, the government does not have any other option than establishing a set of rules that describe a clear secrecy system. The secrecy concept can be framed within the concept of records life cycle, in order to be more adjustable to the existing system